Conditional failure profile analysis for multiple failure modes from incomplete two-dimensionalwarranty data. (October 2022) - Gupta, Sanjib Kumar
This paper addresses the issue of detecting dominating failure modes of a system from a two-dimensional warranty data set by analyzing conditional failure profile of the system. Two testing procedures have been proposed to test whether any of the failure modes is dominating at a particular time interval and whether there is a change of the failure profile from one time interval to another disjoint time interval, conditioning on a given usage layer. Detecting the problematic failure modes early from the conditional failure profile and taking appropriate actions to reduce the conditional failure probability of the system can significantly reduce both tangible and intangible costs of poor reliability in any manufacturing industry. On the other hand, the study of possible changes of conditional failure profiles has a significant role to assess the field performance of items from one time interval to another time interval for a particular choice of usage layer. The utility of this study is explored with the help of a real-life data set.